Carbapenem-resistant Acinetobacter baumannii isolates carrying blaOXA genes with upstream ISAba1: First report of a novel OXA subclass from Iran. (September 2019) - Yazdansetad, Sajjad; Najari, Ehsan; Ghaemi, Ezzat Allah; Javid, Naemeh; Hashemi, Ali; Ardebili, Abdollah
Highlights: High rate of antimicrobial resistance is a great challenge to the treatment of A. baumannii . Polymyxins and tigecycline were the most active agents against A. baumannii in Iran. bla OXA genes and IS Aba1 are a source of carbapenem resistance in A. baumannii . First report of bla OXA-235-like -harboring A. baumannii isolates from Iran. Abstract: Objectives: Carbapenem-resistant Acinetobacter baumannii (CRAB) have emerged as a serious threat to public-health worldwide. This study aimed to determine the antimicrobial susceptibility of A. baumannii isolates in Iran and to investigate oxacillinase-encoding determinants and their association with insertion sequence IS Aba1 in CRAB isolates. Methods: This study was performed on A. baumannii isolates recovered from patients with burn wound infections during 2013. All isolates were evaluated for antimicrobial susceptibility by the disk diffusion method. Minimum inhibitory concentrations (MICs) of five antibiotics (imipenem, meropenem, polymyxin B, colistin and tigecycline) were determined for all CRAB isolates. PCR was performed to determine the distribution of bla OXA determinants and IS Aba1 insertion upstream of each corresponding gene in the CRAB isolates. Results: A total of 65 A. baumannii isolates were recovered during the 1-year period, with CRAB accounting for 63 (96.9%) of isolates. Polymyxin B, colistin and tigecycline were the most effective agents against CRAB isolates, with susceptibility rates of 100%, 87.3% and 65.1%, respectively. The proportion of CRAB isolates carrying oxacillinase determinants was as follow: bla OXA-51-like, 100%; bla OXA-23-like, 74.6%; bla OXA-24/40-like, 47.6%; and bla OXA-235-like, 12.7%. IS Aba1, IS Aba1 – bla OXA-23-like and IS Aba1 – bla OXA-51-like were detected in 100%, 41.3% and 1.6% of CRAB isolates, respectively. Co-occurrence of bla OXA determinants or inserted IS Aba1 upstream of the corresponding genes was associated with increased carbapenem MICs (≥128 μg/mL). Conclusion: The emergence of high-level CRAB with bla OXA and IS Aba1 – bla OXA family in burn patients is a matter of increasing clinical concern, emphasising the need for infection control efforts to limit such problematic bacteria.